IFPRI-ESSP and CGIAR highlight: Key research and youth dialogue at the 22nd international conference on the Ethiopian economy - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
On July 18–19, the 22nd International Conference on the Ethiopian Economy was held at the Ethiopian Economics Association (EEA) Conference Centre. As a co-organizer, the Ethiopia Strategy Support Program (ESSP) of IFPRI, together with the Policy Innovation Program of CGIAR, actively participated in the event.